2001
DOI: 10.1016/s0167-4889(01)00138-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of basal nitric oxide production in living cells

Abstract: Nitric oxide (NO) is an important modulator of immune, endocrine and neuronal functions; however, measuring physiological levels of NO in cell cultures is generally difficult because of the lack of suitable methodologies. We have selected three cell lines from different origins: the neuroblastoma-derived Neuro2A (N2A), the cholinergic SN56 and the non-neuronal COS-1. We first demonstrated the presence of NADPH-diaphoretic activity, a potential marker of the NO-synthesizing (NOS) enzyme. By immunocytochemistry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…5A). At 1 mM carboxy-PTIO (NO-specific scavenger), NO production was significantly abolished in COS-1 cells (López-Figueroa et al 2001). As shown in Fig.…”
Section: No Involvement In Hwc-induced Nr Transcript Accumulationmentioning
confidence: 62%
“…5A). At 1 mM carboxy-PTIO (NO-specific scavenger), NO production was significantly abolished in COS-1 cells (López-Figueroa et al 2001). As shown in Fig.…”
Section: No Involvement In Hwc-induced Nr Transcript Accumulationmentioning
confidence: 62%
“…1B). To confirm that S-nitrosylation not only occurred through the treatment with an exogenous NO donor, we performed a similar experiment with the use of N2A cells, which have been shown to possess endogenous neuronal NO synthase (nNOS) activity (8). After the biotin switch assay on N2A cells transfected with XIAP, we found that XIAP was S-nitrosylated under basal conditions (Fig.…”
Section: Bir Domains Of Xiap Are S-nitrosylated By Nomentioning
confidence: 87%
“…It has been suggested that the major advantage of DAF-2 fluorescence spectroscopy over other NO sensitive imaging/ detection techniques (such as electron paramagnetic resonance or EPR with NO spin trapping) is the ability to detect the basal NO production from endothelial and neuronal cells, with submicromolar NO concentrations (41,49,50). The intracellular level of ascorbate is as high as 9 mM in human endothelial cells (24) and is in the range of 1-10 mM in neurons (25).…”
Section: Discussionmentioning
confidence: 99%